CHEMICAL AND BIOLOGICAL POTENTIAL OF PASSIFLORA VITIFOLIA FRUIT BYPRODUCTS COLLECTED IN THE COLOMBIAN CENTRAL ANDES - AVILA, JENNY; JIMÉNEZ, ANGEL; MÉNDEZ, JONH; MURILLO, ELIZABETH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to establish potential uses of the fruit peel and seeds from Passiflora vitifolia collected in the Colombian Central Andes. Methods: The physical characteristics and chemical profile of the byproducts were determined. The ethanolic extracts of these materials were used to assess the content and phytophenols composition, to establish the antioxidant potential and the antidiabetic activity, in vitro inhibition of α-amylase enzyme and glucose diffusion. The performance and physicochemical composition of the seed oil was also evaluated. Results: The seeds contain almost 4 times more phenolic compounds (10 671 mg GAE/100 g sample) than the peel (2817 mg GAE/100 g sample). Likewise, crude protein and fat contents from the seeds are higher (15.5% and 25.6%) than the peel (6.60% and 5.70%, respectively). Nine phytoconstituents were positive for both extracts. Significant variation (p<0.05) of antioxidant and anti-hyperglycemic potential was observed among the peel and seeds in all methods applied. Conclusion: Results showed that the byproducts of P. vitifolia fruit could be used to enhance the nutritional quality of functional products. These findings were also confirmed by the ethanolic extract from seeds, which revealed high levels of phenolics, high antioxidant potential, and anti-hyperglycemic activity that make it a promising phytotherapeutic product, all of which gives added value to the fruit of this wild Passiflora.